Assessing the application of miscible CO2 flooding in oil reservoirs: a case study from Pakistan - Bhatti, A.A. (Springer Verlag, 2018)
Miscible carbon dioxide (CO2) flooding has been recognized as a promising approach to enhance the recovery of oil reservoirs. However, depending on the injection strategy and rock/fluid characteristics, efficiency of the miscible CO2 flooding varies from reservoir to reservoir. Although, many studies have been carried out to evaluate the performance of the miscible CO2 flooding, a specific strategy which can be strictly followed for a hydrocarbon reservoir has not been established yet. The aim of this study is to assess one of Pakistanâs oil reservoirs for miscible CO2 flooding by applying a modified screening criterion and numerical modeling. As such, the most recent miscible CO2 screening criteria were modified, and a numerical modeling was applied on the prospective reservoir. Based on the results obtained, South oil reservoir (S3) is chosen for a detailed assessment of miscible CO2 flooding. It was also found that implementation of CO2 water-alternating gas (CO2-WAG) injection at early stages of production can increase the production life of the reservoir. Â© 2018 The Author(s)